Serum Albumin Level and Short-Term Outcome Following Stroke in Hospital Admitted Patients (Bangladesh Journal of Medical Biochemistry, 2018)
Albumin is a non-glycosylated plasma protein synthesized primarily in the liver. It is a protein involved in the transport of small molecules in the blood and plays a key role in restricting fluid leakage from the vasculature into the tissue. Elevated level of serum albumin is related to haemoconcentration and reduced level is associated with malnutrition and chronic inflammatory diseases representing a negative acute phase protein. This cross sectional study was done to determine the association between admission serum albumin levels and short-term outcome following acute stroke. Consecutive first-ever acute stroke patients were enrolled between January 2016 and December 2016 at DMCH. On admission serum albumin were measured. Patients were then followed up for 10 days and outcome measure at the end of the study were 10- day mortality. Relationship between serum albumin and stroke outcome was determined. A total of 100 stroke cases were thus included in the study comprising 66 males and 34 females. The mean age of patients was 69.2±12.2 years. Of total, 74% patients were of ischemic stroke and 26% were of hemorrhagic stroke. Among them 22 patients expired in the hospitalization period within 10 days and remaining 78 patients were discharged. The mean serum level of albumin was 2.90±0.57 g/dl in the expired group and 3.79±0.51 g/dl in the discharged group. It may be concluded that low admission serum albumin may be significantly associated with poor outcome.Bangladesh J Med Biochem 2016; 9(1): 27-30